Comments on "Facilitation and Coherence Between the Dynamic and Retrospective Perception of Segmentation in Computer-Generated Music," by Freya Bailes and Roger T. Dean - Ian Cross; Martin Rohrmeier (Empirical Musicology Review, 2007)
Although the study by Bailes & Dean (2007) addresses an underresearched area of auditory and musical perception, it raises questions concerning stimuli, methodology, and the study's relation to previous research, that are outlined in this commentary.